PROBLEMATIC HADITHS IN QURRAH AL-ASHFIYA’ BY KIAI ZAINULLAH MALANG: An Intertextual Analysis - Muhammad Hilal (Riwayah: Jurnal Studi Hadis, 2024)
Qurrah al-Ashfiya’ ‘ala Syarh Nazhm Hidayah al-Adzkiya’ is a manuscript on Sufism written by Kiai Zainullah Malang. The book contains 74 hadiths and, after takhrij was carried out, three of them were found to have no original source in hadith compilation. This research aims to analyze these “problematic hadiths” using intertextual analysis developed by Julia Kristeva. Thus, this research is a hadith research with a multidisciplinary approach. The design used here is library research with a qualitative approach. The analysis technique used here is content analysis. This research finds that there are three problematic hadiths in Qurrah al-Ashfiya’. Through intertextual analysis, it is found that the first hadith is proven to be typographical error and subsequently disqualified as a hadith. The second one is narration bi al-ma‘na. The third one was found to have been inaccurately transcribed by Kiai Zainullah. Furthermore, it is proven that intertextual analysis can be an effective tool for resolving the limitations of takhrij al-hadits. The implication is that since intertextual analysis assumes that a text is always born in a network of multitext, all hadith basically have a source whose origins can be traced. Intertextual analysis does not recognize the term la ashl lahu (no chain of transmission is found).